Hribovske kmetije Slovenjgraškega Pohorja - Gams, Ivan (Geografski zbornik, 1984)
The study deals with the natural geographic conditions and socio-economic state of the 137 mountain farms in the eleven settlements of the Pohorje mountain-range, incorporated into Slovenj Gradec community.
Keywords: geografija; geography; hribovske kmetije; mountain farms; Pohorje; Slovenia; Slovenija